What can we learn about lipoprotein metabolism and coronary heart disease from studying rare variants?. Issue 2 (April 2016) - Jeff, Janina M.; Peloso, Gina M.; Do, Ron
Abstract : Purpose of review: Rare variant association studies (RVAS) target the class of genetic variation with frequencies less than 1%. Recently, investigators have used exome sequencing in RVAS to identify rare alleles responsible for Mendelian diseases but have experienced greater difficulty discovering such alleles for complex diseases. In this review, we describe what we have learned about lipoprotein metabolism and coronary heart disease through the conduct of RVAS. Recent findings: Rare protein-altering genetic variation can provide important insights that are not as easily attainable from common variant association studies. First, RVAS can facilitate gene discovery by identifying novel rare protein-altering variants in specific genes that are associated with disease. Second, rare variant associations can provide supportive evidence for putative drug targets for novel therapies. Finally, rare variants can uncover new pathways and reveal new biologic mechanisms. Summary: The field of human genetics has already made tremendous progress in understanding lipoprotein metabolism and the causes of coronary heart disease in the context of rare variants. As next generation sequencing becomes more cost-effective, RVAS with larger sample sizes will be conducted. This will lead to more novel rare variant discoveries and the translation of genomic data into biological knowledge and clinical insights for cardiovascular disease.